Opportunities for AI Development in the Accounting Domain: The Case for Auditing - Baldwin,Amelia A; Brown,Carol; Trinkle,Brad S (Intelligent Systems in Accounting, Finance and Management, 2006)
This paper reviews the nature of accounting and auditing problems and the need for application of Artificial Intelligence (AI) technologies to the discipline. The discussion includes current accounting issues for which new AI development should be fruitful particularly auditing and assurance.
Keywords: Accounting; Dean's Office